WEB based system for analysing mathematics learning results of students - Janilionis, Vytautas; Baltutis, Mindaugas (Lietuvos matematikos rinkinys, 2003)
The data analysis models of mathematics learning results and web based software are presented in this paper. The models and software were developed using statistical methods (descriptive statistics, analysis of variance, nonparametric tests and correlation analysis) and object programming technologies of webAF and webEIS for Java applets, as components of SAS AppDev Studio. The developed system is used for the analysis of mathematics learning results in Kaunas University of Technology. It enables to analyze the relationships and dependencies between various factors (e.g., study areas, faculties, form of studies, math exams grades etc.) and use the results for the effective decision-making.